Segmentasi Citra Berbasis Clustering Menggunakan Algoritma Fuzzy C-Means - Budi Adnyana, I Made; Darmaputra, IKetut Gede; Bayupati, I Putu Agung (Jurnal Teknologi Elektro; Vol 14 No 1 (2015): (January - June) Majalah Ilmiah Teknologi Elektro, 2015)
Clustering based image segmentation in this study using Fuzzy C means algorithm with Xie Beni Index as an objective function. Preprocessing applied in this model using Statistical Region merging. Spatial function applied in Fuzzy C means method to reduce noise in clustering. The system evaluation is done by measuring cluster validity value (Xie Beni Index), execution time, and number of iteration. Experimental results on three test images illustrates the proposed method able to perform image segmentation well.
Keywords: image segmentation, fuzzy c-means, clustering